Commentary: Moment of (Perceived) Truth: Exploring Accuracy of Aha! Experiences. (26th December 2019) - Webb, Margaret E.; Laukkonen, Ruben E.; Cropper, Simon J.; Little, Daniel R.
Abstract: Danek and Salvi ( The Journal of Creative Behavior, 1–3, 2018) provide a sound overview of research on the relationship between feelings of aha and the accuracy of problem‐solving solutions. However, there are reasons to be cautious in concluding that a characteristic of insightful solutions is their superior accuracy. A relationship between correct solutions and aha experiences clearly exists in the literature. However, the strength and frequency of aha experiences seem to be variable across individuals and can be manipulated. We provide a brief overview of some literature that challenges the claim that aha experience indicates accurate solutions, particularly, manipulations of aha experiences, metacognitive misattributions and erroneous insights, and dispositions toward insight.